Here Lives a Wealthy Man: Price Rigidity and Predictability in Luxury Housing Markets - Daniel Levy; Avichai Snir (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
We use novel and unique data to study the effect of price changes in the market for luxury and middle class homes. We find that luxury home sales respond less to price changes than the middle-class home sales; in the market for luxury homes, past prices affect current prices; luxury home prices persist; and prices of luxury homes are stickier than prices of middle-class homes. Recent macroeconomic models predict that housing markets can have counter-cyclical effect, if home prices are flexible. Our findings imply that home prices, especially luxury home prices, may not be flexible enough to generate such effect.
Keywords: E31; E32; R21; G14; D12; 330; Housing market; Luxury housing; Housing demand; Price rigidity; Sticky prices; Predictability; Veblen Effect